2016
DOI: 10.2298/vsp150514093p
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and metabolic syndrome as risk factors for the development of non-alcoholic fatty liver disease as diagnosed by ultrasound

Abstract: The results of our study have confirmed that a high percentage of patients with high risk factors (DM, MS, dyslipidemia, hypertension) have NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…Dyslipidaemia is a well-established risk factor for NAFLD. 62 In fact, patients with NAFLD usually have an atherogenic dyslipidaemia characterised by high levels of TG, LDL cholesterol and VLDL cholesterol, as well as a higher concentration of remnant lipoprotein cholesterol coupled with low HDL cholesterol levels. 63 64 In this context, due to an increased cardiovascular risk, the treatment of dyslipidaemia should be considered in the management framework of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Dyslipidaemia is a well-established risk factor for NAFLD. 62 In fact, patients with NAFLD usually have an atherogenic dyslipidaemia characterised by high levels of TG, LDL cholesterol and VLDL cholesterol, as well as a higher concentration of remnant lipoprotein cholesterol coupled with low HDL cholesterol levels. 63 64 In this context, due to an increased cardiovascular risk, the treatment of dyslipidaemia should be considered in the management framework of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…There are 39% of women and 39% of men aged ≥18 overweight and 18% of overweight or obese children and adolescents in 2016 [2]. Insulin resistance and dyslipidemia induced by obesity and diabetes are risk factors for the occurrence of nonalcoholic fatty liver disease (NAFLD) [3,4]. How to prevent and improve obesity and diabetes has become an important issue to reduce the prevalence of NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…A positive association was observed between red meat and NAFLD in males, perhaps it is because males had a higher meat intakes and a higher prevalence of fatty liver than females [39]. Moreover, several studies had found signi cant associations of high meat intakes with obesity, type 2 diabetes and hypertension [14,17,40], which were considered as risk factors in the development of NAFLD [19,41,42]. In our study, positive association of red meat intake with NAFLD was found in people with BMI≥24 kg/m 2 and people with hypertension.…”
Section: Discussionmentioning
confidence: 99%